The oldest known clerid fossils from the Middle Jurassic of China, with a review of Cleridae systematics (Coleoptera). (5th September 2016) - KOLIBÁČ, JIŘÍ; HUANG, DIYING
Abstract: Three fossil beetles recorded from Inner Mongolia, China (Callovian, Middle Jurassic, approximately 165 Ma) are assigned to Cleridae and constitute the earliest known representatives of this family. Two of the fossils are described as Protoclerus korynetoides gen. et sp.n. and the third as Wangweiella calloviana gen. et sp.n. Ninety‐six morphological characters of the larvae and adults of 17 extant clerid representatives and seven cleroid families as outgroups were analysed under maximum parsimony with, and without, fossil species included in the matrix. The results indicate that Protoclerus gen.n. is a separate lineage within the family, whereas Wangweiella gen.n. is sister to the rest of Epiclininae. The resulting trees are compared with the most recent morphological and molecular phylogenies of Cleridae. The trees presented appear congruent with the latest molecular phylogenies. The evolution of Cleridae, as well as their biogeography and systematics, are briefly reviewed. A complete list of clerid fossil species described to date is provided. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:32240D3D-2A7A-41F6-B485-A66F2265CB8A .